Model transformation as a mechanism for the implementation of domain specific transformation languages - Irazábal, Jerónimo
Model Driven Engineering proposes a software development process in which the key notions are models and model transformations. Model transformations are specified using a model transformation language. There are already several proposals for model transformation specification, implementation, and execution, which are beginning to be used by Model Driven Engineering practitioners. The term model transformation language comprises all sorts of artificial languages used in model transformation development such as QVT, ATL and RubyTL. These languages are specific to define model transformations; however an extra level of specialization can be realized on them. That is to say, we can define a transformation language specifically addressed to a given transformation domain. In the present work we introduce the proposal of defining domain specific transformation languages and also we analyze a novel way to define their semantics. Our proposal consists in using transformation languages themselves to the implementation of such domain specific languages. We illustrate the proposal through an example in the data base domain.